Examining the quality of life of adults with chronic mental distress: An empirical study in two mental health centres in Athens - Ευαγγέλου, Εβίτα (The Greek Review of Social Research, 2014)
Quality of life (QOL) is a matter of concern for people who are diagnosed with persistent mental distress. This paper presents the qualitative findings of a PhD project, which examined the QOL perceptions of 44 adults diagnosed with schizophrenia, manic depressive disorder or compulsive depressive disorder, who attended two Community Mental Health Centres, in Athens. The study employed a combined method using two standardized QOL instruments and 22 semi-structured interviews. Qualitative outcomes indicated that the participants’ representations of their care environments were positive, they participated in decisions regarding their medical treatment and their involvement in the MHCs had a positive impact on their social and intimate relationships. In terms of personal meaning of QOL, participants referred to objective QOL indicators, and further to a number of internal standards related to creativity and personal growth.